Determinants of Sustainable Competitive Advantage in SMEs: A Systematic Review Based on the Resource-Based View and Dynamic Capabilities Perspectives - Rina Ekawati; Ari Djanuar Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to identify the primary determinants of sustainable competitive advantage (SCA) in small and medium-sized enterprises (SMEs) through a systematic literature review based on the PRISMA 2020 protocol. By integrating the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT), this study synthesizes 55 peer-reviewed international journal articles indexed in Scopus and Web of Science published between 2015 and 2026. The findings reveal eight key determinants categorized into internal and external factors. Internal factors include VRIN resources, innovation capability, human capital, and entrepreneurial orientation. External factors comprise digital transformation, business ecosystems, market turbulence, and institutional support. The results indicate that the integration of RBV and DCT provides greater explanatory power than the partial application of either theory alone, particularly for SMEs operating under resource constraints and high environmental dynamism. This study contributes to the development of an integrative conceptual model and proposes a future empirical research agenda grounded in the context of emerging economies.